Intersecting religion and sexuality: sociological perspectives - Page, Sarah-Jane; Yip, Andrew K. T. (Religion and the social order, 2020)
This edited collection, Intersecting Religion and Sexuality: Sociological Perspectives , outlines what an intersectional analysis can offer research into religion and sexuality. It draws on various research projects which focus on different facets of this topic, such as queer sexualities, unmarried motherhood and heterosexuality, to explore how religion and sexuality intersect with each other, and with other identities such as ethnicity, gender and social class. Given the predominantly heteronormative nature of many religious traditions, marginality, power dynamics and inequalities are central to these interrogations. Intersectionality is an important theoretical lens through which to explore identities that are variously impacted by particular power dynamics and axes of privilege and disadvantage